Models of supply chain management in the efforts to develop the banyumasan batik industry - Susanti, Marcely; Nurlaili, Nurlaili; Darmawan, Rachmat (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
Inventory of raw materials is one of the crucial problems in the company. Errors in determining the size of raw material inventory is very influential for the smooth production of the company. PT Semen Bosowa Maros is a private company that focuses on cement production. This study aims to avoid excess and shortage of raw materials by calculating the amount of raw material inventory at PT Semen Bosowa Maros. This study uses the Min-Max Stock method. The research data was obtained from the company's annual data with related parties. The results of the study obtained safety stock values of Silica Sand 166.46 ton’s, Gypsum 1482.96 ton’s, Fly Ash 33.71 ton’s, and Trass 30.76 ton’s. Then, the minimum inventory calculation is carried out, it is known that the minimum inventory results are found in Trass raw materials of 260.18 ton’s while the results for maximum inventory are in Gypsum of 22117.18 ton’s. After calculating the min-max, an order policy can be obtained for each material, Silica Sand 1074.85 ton’s, Gypsum 9575.63 ton’s, Fly Ash 217.68 ton’s, and Trass 198.65 ton’s.